2012
DOI: 10.1007/s10571-012-9800-z
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the Stomach: Corticotropin-Releasing Factor May Protect the Gastric Mucosa in Stress Through Involvement of Glucocorticoids

Abstract: Stress may contribute to the development of gastric ulcer disease. The results of our previous investigations suggest that glucocorticoids released during acute stress act as gastroprotective hormones, and not as ulcerogenic agents as has been generally accepted for a long time. In this study, we investigated whether corticotropin-releasing factor (CRF) may protect the gastric mucosa against stress-induced gastric injury through involvement of glucocorticoids. Intraperitoneal administration of CRF (1.25 μg/kg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Taking into consideration this fact together with the facts that humoral pathway and systemic response are two main pathways for the transmitting the RIPC-induced protective signals ( Lim and Hausenloy, 2012 ) it is reasonable to propose a participation of glucocorticoids in realization of gastroprotective effect of RIPC. Our previous findings about gastroprotective role of glucocorticoids also allowed us to assume that glucocorticoids may contribute to gastroprotective effect of RIPC ( Filaretova et al, 1998 ; Filaretova et al, 2004 ; Filaretova et al, 2007 ; Filaretova et al, 2008 , Filaretova et al, 2012 ; Filaretova, 2011 ; Filaretova, 2017 ; Filaretova and Bagaeva, 2016 ). Additionally it is important to note that we previously demonstrated participation of glucocorticoids in protective effect of local gastric ischemic preconditioning against I/R-induced gastric injury ( Bobryshev et al, 2009 ).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Taking into consideration this fact together with the facts that humoral pathway and systemic response are two main pathways for the transmitting the RIPC-induced protective signals ( Lim and Hausenloy, 2012 ) it is reasonable to propose a participation of glucocorticoids in realization of gastroprotective effect of RIPC. Our previous findings about gastroprotective role of glucocorticoids also allowed us to assume that glucocorticoids may contribute to gastroprotective effect of RIPC ( Filaretova et al, 1998 ; Filaretova et al, 2004 ; Filaretova et al, 2007 ; Filaretova et al, 2008 , Filaretova et al, 2012 ; Filaretova, 2011 ; Filaretova, 2017 ; Filaretova and Bagaeva, 2016 ). Additionally it is important to note that we previously demonstrated participation of glucocorticoids in protective effect of local gastric ischemic preconditioning against I/R-induced gastric injury ( Bobryshev et al, 2009 ).…”
Section: Introductionmentioning
confidence: 84%
“…It was not assumed before to verify the participation of glucocorticoids in gastroprotective effect of RIPS, apparently due to the prevailing traditional point of view on ulcerogenic action of glucocorticoids released during stress. Nevertheless, our previous findings suggest that glucocorticoids released during acute stress-induced activation of the hypothalamic-pituitary-adrenocortical (HPA) axis are naturally occurring protective factors that play an important role in maintenance of the gastric mucosal integrity ( Filaretova et al, 1998 ; Filaretova et al, 2012 ; Filaretova 2011 ; Filaretova and Bagaeva 2016 ). It was demonstrated that glucocorticoids released during preconditioning mild stress contribute to the protective effect of this stress on gastric mucosa against cold-restraint-induced gastric lesions ( Filaretova et al, 2008 ; Filaretova, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gastroprotective effect of CRF was also prevented by the pretreatment of rats with RU-38486. The results obtained suggest that CRF-induced glucocorticoids contribute to gastroprotective action of CRF [ 69 ]. The findings further support the idea about gastroprotective role of stress-produced glucocorticoids.…”
Section: The Hpa Axis As a Hormonal Branch Of The Brain-gut Interactimentioning
confidence: 99%
“…It is important to understand the mechanism by which stress‐induced gastric injury develops because it may be useful for the prevention and treatment of stress‐related organ injury. Several factors are known to play a role in the development of stress‐induced gastric injury, including reactive oxygen species, bioactive amines, and cytokines 1–3 . Although a variety of pro‐inflammatory cytokines, including tumor necrosis factor‐α (TNF‐α), interleukin (IL)‐1β, IL‐6, and IL‐18, are upregulated in the stomach after stress treatment, 4–6 the functional role of these cytokines in the development of stress‐induced gastric injury is not well understood.…”
Section: Introductionmentioning
confidence: 99%